The Correlation between Pre-service Teachers' Attitudes towards Technology and Achievement in Material Design Course - Findikoglu, Fuat; Alci, Bulent; Karatas, Hakan (KAMLA-RAJ ENTERPRISES, 2015)
This study aims to specify the correlation between pre-service teachers' attitudes towards technology and achievement in material design. The participants of the study consisted of 127 pre-service teachers from different disciplines. To determine the attitudes of pre-service teachers, data was collected using the Technology Attitude Scale. The achievement scores of pre-service teachers in material design were obtained using the material evaluation form developed by the researchers based on the principles of designing material. While evaluating the data, analyses of Pearson correlation and t-test were conducted, the results revealed a positive correlation between pre-service teachers' attitudes towards technology and achievement in material design. Also, significant differences were found according to pre-service teachers' disciplines. These findings and implications for educational researchers were also further discussed.
Keywords: Pre-service Teachers; Technology Use; Attitudes towards Technology; Academic Success; INSTRUCTIONAL-TECHNOLOGY; PERCEPTIONS; ICT; COMPUTERS; EDUCATION; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics